On the Right of Economic Operators to Provide Evidence to Demonstrate their Reliability - Goranova, Ilonka (Research Papers, 2020)
The aim of the following paper is to illustrate the legal courses of action for economic operators to demonstrate their reliability in the performance of public procurement contracts despite the existence of a relevant ground for exclusion, through practical oriented analysis of the current European and Bulgarian legislation. The main tasks of the research are: review of the admissible self-cleaning measures and analysis of the obligation of contracting authorities to assess the extent to which those measures are sufficient to fulfill their intended purpose. It is emphasized on the importance of the requirement the reasons for the contracting authority's acceptance or reject of the measures undertaken by the economic operator, to be stated. The contracting authority is to bear the consequences of a possible erroneous decision. The burden of proof that there is a ground for exclusion of the economic operator from further participation rests on the contracting authority.
Keywords: Public procurement; Self-cleaning measures; Grounds for еxclusion